Persistence, Fate, and Effectiveness of Dispersants used during the Deepwater Horizon Oil Spill - Monica Wilson; Larissa Graham; Christine Hale; Emily Maung-Douglass; Stephen Sempier; LaDon Swann (EDIS)
The Deepwater Horizon (DWH) oil spill was the first spill that occurred in the deep ocean, nearly one mile below the ocean’s surface. The large-scale applications of dispersants used at the surface and wellhead during the Deepwater Horizon oil spill raised many questions and highlighted the importance of understanding their effects on the marine environment.